2009
DOI: 10.2320/matertrans.mra2008343
|View full text |Cite
|
Sign up to set email alerts
|

Positive Deviation from a Hall-Petch Relation in Nanocrystalline Aluminum

Abstract: The grain size dependence of yield stress has been investigated for nanocrystalline (nc) bulk aluminum produced by hot extrusion of ballmilled powders. The Hall-Petch slope is positively deviated as the grain size is reduced below 60 nm. For the specific grain size range from 60 nm down to 48 nm, structural analyses and estimation of deformation mechanism exhibit that perfect dislocation emission critically governs deformation of nc aluminum, since the inherent aluminum properties of high stacking fault energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…As a consequence, a maximum threshold value of yield stress or hardness is generally reached at certain grain size level for a given nanocrystalline metal or alloy. Numerous reports show that the transition of positive to negative slope in the HP relationship is around 10-40 nm for varied nanocrystalline metals and alloys [6][7][8], such as Al [9][10][11], Fe [12], Cu [6,13,14], Cu-Ta [15], Ni [6], Ni-P [13], Zr [16], and Zn [17] among others.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, a maximum threshold value of yield stress or hardness is generally reached at certain grain size level for a given nanocrystalline metal or alloy. Numerous reports show that the transition of positive to negative slope in the HP relationship is around 10-40 nm for varied nanocrystalline metals and alloys [6][7][8], such as Al [9][10][11], Fe [12], Cu [6,13,14], Cu-Ta [15], Ni [6], Ni-P [13], Zr [16], and Zn [17] among others.…”
Section: Introductionmentioning
confidence: 99%
“…As noted in Fig. 5, in this region, the yield stress of NC aluminum [22,24] does follow the dependence of d −1 rather than d −1/2 . As the grain size is further reduced to below 40nm, the calculated resolved shear stress for a partial dislocation becomes lower than that of a perfect dislocation, as shown in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…In addition, it has also been experimentally observed that partial dislocations emitted from grain boundaries can travel the grain interior for thin films [9] and powders produced by cryogenic ball milling [13,21]. However, an experimental study using an extruded NC aluminum bulk has reported results that are completely opposite to a positive deviation from the Hall-Petch relation [22]. Recently, UFC aluminum fabricated by accumulative roll bonding has exhibited limited uniform elongation and unexpected yield-drop-like phenomenon [23], while it has not been observed in UFC aluminum having undergone powder metallurgy with similar grain sizes [24].…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations